2008
DOI: 10.1089/adt.2008.148
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening Platform for Anticancer Therapeutic Drug Cytotoxicity

Abstract: There are substances that kill cancer cells, but induce T cell proliferation, like thalidomide. To find more of these, a new anticancer drug screening strategy is vital. In this study we report the development of a differential cytotoxicity screening or evaluation platform using the CellTiter-Glo (Promega, Annandale, NSW, Australia) luminescent cell viability assay (ATP assay) and also the CellTiter 96 AQueous (Promega) one solution cell proliferation assay [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Tissue inhibitors of MMP (TIMP3), which is up-regulated after berberine expose in MCF-7 cells, has been recognized as potential inhibitors of angiogenesis and cancer invasion and metastasis (Ahonen et al, 2002). Interestingly, it demonstrated that berberine suppressed the activities of MMP1, MMP2, MMP9 (Sekhon et al, 2008;Kim et al, 2012), therefore, our results suggested that berberine inhibited the activities of MMPs may be via up-regulation of TIMP3 expression. SLC7A11, which mediates cystine -glutamate exchange and thereby regulates intracellular glutathione (GSH) levels, play an important role in maintaining the higher GSH and consequently in cisplatin resistance (Okuno et al, 2003).…”
Section: 6089 Genomic Screening For Targets Regulated By Berberine Imentioning
confidence: 55%
See 1 more Smart Citation
“…Tissue inhibitors of MMP (TIMP3), which is up-regulated after berberine expose in MCF-7 cells, has been recognized as potential inhibitors of angiogenesis and cancer invasion and metastasis (Ahonen et al, 2002). Interestingly, it demonstrated that berberine suppressed the activities of MMP1, MMP2, MMP9 (Sekhon et al, 2008;Kim et al, 2012), therefore, our results suggested that berberine inhibited the activities of MMPs may be via up-regulation of TIMP3 expression. SLC7A11, which mediates cystine -glutamate exchange and thereby regulates intracellular glutathione (GSH) levels, play an important role in maintaining the higher GSH and consequently in cisplatin resistance (Okuno et al, 2003).…”
Section: 6089 Genomic Screening For Targets Regulated By Berberine Imentioning
confidence: 55%
“…The cell viability was determined by MTS ((Promega, Madison, WI) assay (Sekhon et al, 2008). Briefly, 5×10 3 cells per well were seeded in 96-well culture plates in triplicate and allowed to attach overnight.…”
Section: Mts Assaymentioning
confidence: 99%
“…In identical parallel assays, FLT-MP formation was compared with cellular ATP generation, measured using the CellTiter-Glo ® assay. ATP generation is well-correlated with the number of viable cells in a culture cell, and this endpoint assay is widely used as a surrogate measure of cell proliferation [27]. As shown in Fig.…”
Section: Comparison With Established Methodsmentioning
confidence: 99%
“…To this purpose, new non-radioactive kits are disposable for valuation of specific T-lymphocyte cytotoxicity. These methods provide a measurement of cytotoxicity by using an indirect indicator, such as the release of LDH [144] or ATP enzyme [145], or by the capacity of viable cells to incorporate alamar blue dye, an indicator of cell metabolic activity [146]. Cytolytic activity can also be assayed by flow cytometry that allows quantitative measurements further distinguishing between apoptosis and necrosis.…”
Section: Basis Of Methods Estimated Sensitivity (Antigen-specific:totamentioning
confidence: 99%